Decoding The Layers of Meanings In A Poem Small Kindnesses By Danusha Laméris: A Barthesian Reading - Aliya Syifa Kurnia; R. Myrna Nur Sakinah (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: This article aims to examine the forms of representation of Roland Barthes' narrative codes in Danusha Laméris' poem Small Kindnesses. The narrative codes are: Hermeneutic Code, Proairetic Code, Semantic Code, Symbolic Code, and Cultural Code. The aim of identifying these codes is to discover the implied meaning in addition to the literal meaning of a discourse. As Barthes in his modern semiotic theory proposed connotative meaning in addition to denotative meaning. This research uses a step-by-step qualitative approach by following the way Barthes explored the novel Sarrasine in his book when he introduced the theory of narrative codes. The outcome of the study reveals that in the poem Small Kindnesses, five narrative codes are used in it to achieve connotative meaning or hidden meaning. The result of this meaning is how Small Kindnesses carries social, structural, as well as religious messages as a poem. Keywords: danusha laméris, connotative meaning, narrative codes, small kindnesses, roland barthes.